Control of the rhizobium–legume symbiosis by the plant nitrogen demand is tightly integrated at the whole plant level and requires inter-organ systemic signaling - Lepetit, Marc; Brouquisse, Renaud (Frontiers in Plant Science, 2023)
Symbiotic nodules formed on legumes roots with rhizobia fix atmospheric N2. Bacteria reduce N2 to NH4+ that is assimilated into amino acids by the plant. In return, the plant provides photosynthates to fuel the symbiotic nitrogen fixation. Symbiosis is tightly adjusted to the whole plant nutritional demand and to the plant photosynthetic capacities, but regulatory circuits behind this control remain poorly understood. The use of split-root systems combined to biochemical, physiological, metabolomic, transcriptomic and genetic approaches revealed that multiple pathways are acting in parallel. Systemic signaling mechanisms of the plant N-demand are required for the control of nodule organogenesis, mature nodule functioning and nodule senescence. N satiety/N deficit systemic signaling correlates to rapid variations of the nodules sugar levels, tuning symbiosis by C resources allocation. These mechanisms are responsible for the adjustment of plant symbiotic capacities to the mineral N resources. On the one hand, if mineral N can satisfy the plant N-demand, nodule formation is inhibited, and nodule senescence is activated. On the other hand, local conditions (abiotic stresses) may impair symbiotic activity resulting to plant N-limitation. In these conditions, systemic signaling may compensate the N-deficit by stimulating symbiotic root N-foraging. In the past decade, several molecular components of the systemic signaling pathways controlling nodule formation have been identified, but a major challenge remains to understand their specificity as compared to the mechanisms of non-symbiotic plants which control root development and how they contribute to the whole plant phenotypes. Less is known about the control of mature nodule development and functioning by N and C nutritional status of the plant, but an hypothetic model involving the sucrose allocation to the nodule as a systemic signaling process , the oxidative pentose phosphate pathway and the redox status as potential effectors of this signaling is emerging. This work highlights the importance of organism integration in plant biology.